Distribution and diversity of fungi in freshwater sediments on a river catchment scale - Liu, Jie; Wang, Jianan; Gao, Guanghai; Bartlam, Mark G.; Wang, Yingying (Frontiers in Microbiology, 2015)
Fungal communities perform essential functions in biogeochemical cycles. However, knowledge of fungal community structural changes in river ecosystems is still very limited. In the present study, we combined culture-dependent and culture-independent methods to investigate fungal distribution and diversity in sediment on a regional scale in the Songhua River catchment, located in North-East Asia. A total of 147 samples over the whole river catchment were analyzed. The results showed that compared to the mainstream, the tributaries have a higher fungal community organization and culturable fungal concentration, but possess lower community dynamics as assessed by denaturing gradient gel electrophoresis (DGGE). Furthermore, phylogenetic analysis of DGGE bands showed that Ascomycota and Basidiomycota were the predominant community in the Songhua River catchment. Redundancy analysis revealed that longitude was the primary factor determining the variation of fungal community structure, and fungal biomass was mainly related to the total nutrient content. Our findings provide new insights into the characteristics of fungal community distribution in a temperate zone river at a regional scale, and demonstrate that fungal dispersal is restricted by geographical barriers in a whole river catchment.